Meta-analysis of proportion estimates of Extended-Spectrum-Beta-Lactamase-producing Enterobacteriaceae in East Africa hospitals. Issue 1 (December 2016) - Sonda, Tolbert; Kumburu, Happiness; van Zwetselaar, Marco; Alifrangis, Michael; Lund, Ole; Kibiki, Gibson; Aarestrup, Frank
Abstract Background A high proportion of Extended-Spectrum-Beta-Lactamase (ESBL) producingEnterobacteriaceae is causing common infections in all regions of the world. The burden of antibiotic resistance due to ESBL in East Africa is large but information is scarce and thus it is unclear how big the problem really is. To gain insight into the magnitude and molecular epidemiology of ESBL-producingEnterobacteriaceae in East Africa a literature search was performed in PubMed on 31 July 2015 to retrieve articles with relevant information on ESBL. Methods and results Meta-analysis was performed to determine overall proportion estimate of ESBL-producingEnterobacteriaceae . A total of 4076 bacterial isolates were included in the analysis. The overall pooled proportion of ESBL-producingEnterobacteriaceae among included surveys done in East African hospitals was found to be 0.42 (95 % CI: 0.34–0.50). Heterogeneity (I2 ) between countries' proportions in ESBL was significantly high (96.95 % andp  < 0.001). The frequently detected genes encoding ESBL were CTX-M, TEM, SHV and OXA while the most infrequent reported genes were KPC and NDM. Conclusion The available studies show a very wide variation in resistance due to ESBL between countries. This highlights a need for active surveillance systems which can help understand the actual epidemiology of ESBL, aid in formulating national or regional guidelines for proper screening of ESBL, and support developing standardized approaches for managing patients colonized with ESBL.